(untitled) (International journal of medical sciences, 2026)
This review article summarizes current experimental and clinical data on the medicinal properties of clove (Syzygium aromaticum) and its potential use in dentistry. The phytochemical composition of clove is examined, with an emphasis on eugenol and other biologically active compounds with antimicrobial, anti-inflammatory, antioxidant, and analgesic properties. The results of in vitro and in vivo studies demonstrating the activity of clove extracts against key periodontal pathogens and cariogenic microflora are analyzed. Particular attention is given to clinical studies confirming the efficacy of clove oil and its derivatives in the treatment of toothache, gingivitis, stomatitis, and as components of dental materials. Clove-based preparations are shown to have high preventive and therapeutic potential; however, standardization and further clinical trials are required to expand their use in evidence-based dentistry.